Inter-Unit Executive Redeployment in Multiunit Firms: Evidence from Korean Business Groups - Chang, Sea-Jin; Kim, Young-Choon; Park, Sangchan (Organization Science, 2024)
Building on the literature on resource reconfiguration theory, we formulate a new theoretical framework that explains how executive redeployment within a diversified firm transfers different types of human capital embodied in executives to different units facing specific business challenges. In the empirical context of Korean business groups, we find that executives with unit-specific human capital, like turnaround experience, competitive experience, and international expansion experience, are redeployed to units with corresponding business challenges like financial difficulties, intensifying competition, and early-stage international expansion, respectively. We also show that executives with unit-generic human capital, like corporate management practices and interunit coordination experiences, are redeployed to younger units seeking to establish corporate-level policies and practices. Additional analyses also show that the value of firm-specific human capital in driving the redeployment of executives is contingent on their functional orientation and seniority. Funding: S.-J. Chang appreciates financial support from the Lim Kim San Chair Professorship from National University of Singapore and Techno SK Chair Professorship from KAIST. Y.-C. Kim is also grateful for financial support from the Ministry of Education of the Republic of Korea and the National Research Foundation of Korea [NRF-2022S1A5A2A01044597]. Supplemental Material: The e-companion is available at https://doi.org/10.1287/orsc.2020.14525 .